Criteria for evaluating the environmental impact on the mining sector - Soriano Parra, Lady (2015)
Peru is a mining country par excellence, by which many mining companies exploit these resources. In making these activities generates impact the environment concerning the flora, fauna, socio-economics, etc. That is why the Ministry of Environment evaluates the environmental impact by parameters such as size, nature, which must give the final result if it is viable or not to continue with the mining project. The process of evaluation of environmental impact can last for months, even years. This article proposes criteria for environmental impact assessment in the mining sector may serve to support decision making.